Haemodynamics during a complete exercise induced atrioventricular block. Issue 1 (1st February 2002) - Crisafulli, A; Melis, F; Lai, A C; Orrù, V; Lai, C; Concu, A
Abstract : The case is reported of an athlete who, during an exercise test, had a complete atrioventricular block without symptoms of cardiac output failure. Heart rate, stroke index, cardiac index, and myocardial contractility were monitored during the episode by an impedance cardiograph. The most important findings of this report are the continuous increase in stroke index, which compensated for the lack of heart rate response, and the normal cardiac index values achieved during the exercise. This stroke index response was mainly due to an increase in myocardial contractility.